2023
DOI: 10.1097/md.0000000000034940
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based metabolism-related genes signature, single-cell RNA sequencing, and experimental validation in hypersensitivity pneumonitis

Jie He,
Bo Wang,
Meifeng Chen
et al.

Abstract: Metabolism is involved in the pathogenesis of hypersensitivity pneumonitis. To identify diagnostic feature biomarkers based on metabolism-related genes (MRGs) and determine the correlation between MRGs and M2 macrophages in patients with hypersensitivity pneumonitis (HP). We retrieved the gene expression matrix from the Gene Expression Omnibus database. The differentially expressed MRGs (DE-MRGs) between healthy control (HC) and patients with HP were identified using the “DESeq2” R package. The “clusterProfile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Exposure to hyperoxia for 72 h has been shown to increase GPX3 protein levels in both the plasma and lungs of mice, suggesting a protective response to oxidative stress [ 128 ]. He et al identified GPX3 as a potential diagnostic biomarker for patients with hypersensitivity pneumonitis [ 129 ]. Additionally, Marko Markovic revealed a significant association between the GPX3 rs8177412 variant genotype and the risk of developing severe forms of COVID-19, suggesting that GPX3 is a complementary diagnostic tool for predicting the disease course [ 130 ].…”
Section: Research Progress In Gpx3 and Non-neoplastic Diseasesmentioning
confidence: 99%
“…Exposure to hyperoxia for 72 h has been shown to increase GPX3 protein levels in both the plasma and lungs of mice, suggesting a protective response to oxidative stress [ 128 ]. He et al identified GPX3 as a potential diagnostic biomarker for patients with hypersensitivity pneumonitis [ 129 ]. Additionally, Marko Markovic revealed a significant association between the GPX3 rs8177412 variant genotype and the risk of developing severe forms of COVID-19, suggesting that GPX3 is a complementary diagnostic tool for predicting the disease course [ 130 ].…”
Section: Research Progress In Gpx3 and Non-neoplastic Diseasesmentioning
confidence: 99%